2002
DOI: 10.1159/000048017
|View full text |Cite
|
Sign up to set email alerts
|

Myomectomy as a Pregnancy-Preserving Option in the Carefully Selected Patient

Abstract: Objectives: To present the indications for myomectomy during pregnancy and to discuss complications possibly related and unrelated to the procedure. Method and Results: A 33-year-old patient at 18 weeks of gestation underwent removal of a 1,570-gram symptomatic fundic myoma. Histologically the patient had a leiomyomatous neoplasm of uncertain malignant potential. The pregnancy was continued under sequential observation with magnetic resonance imaging and ultrasound. At 36 weeks of gestation a healthy girl with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…The risk of miscarriage, pPROM or preterm birth in women with fibroids undergoing amniocentesis is not increased compared with the general population, especially if antibiotic prophylaxis is used. The increased rate of fetal loss in patients with myoma is to attribute only to the fibroids themselves, and amniocentesis does not increase this risk …”
Section: Obstetric Complications Of Myomas During Pregnancymentioning
confidence: 99%
“…The risk of miscarriage, pPROM or preterm birth in women with fibroids undergoing amniocentesis is not increased compared with the general population, especially if antibiotic prophylaxis is used. The increased rate of fetal loss in patients with myoma is to attribute only to the fibroids themselves, and amniocentesis does not increase this risk …”
Section: Obstetric Complications Of Myomas During Pregnancymentioning
confidence: 99%
“…Such complications include necrobiosis with pains, abortions, preterm premature rupture of the membranes, preterm deliveries, abnormal lies and presentations, increased caesarean delivery rates, postpartum haemorrhage and endomyometritis 1 .In order to prevent these complications some have performed antenatal myomectomies in selected cases 2 . Huge uterine myomas are not frequent encounters in Post Partum Haemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by degeneration of the myoma due to reduced perfusion, which occurs frequently and may be associated with nausea, vomiting and fever [17]. If the pain is resistant to treatment, some authors consider that myoma enucleation is indicated in the pregnant uterus.…”
Section: Discussionmentioning
confidence: 99%